Death in the A Shau Valley : L Company LRRPs in Vietnam, 1969-70 - Chambers, Larry, 1947- (New York : Ivy Books, 1998)
'The enemy had a single purpose: kill me and my teammates.' Larry Chambers was still new to Vietnam in early 1969 when the LRRPs of the 101st Airborne Division became L Company, 75th (Rangers). But his unit's mission stayed the same: act as the eyes and ears of the 101st deep in the dreaded A Shau Valley--where the NVA ruled. Relentless thick fog frequently made fighter bombers useless in the A Shau, and the enemy had furnished the nearby mountaintops with antiaircraft machine guns to protect the massive trail network that snaked through it. So, outgunned, outmanned, and unsupported, the teams of L Company executed hundreds of courageous missions. Now, in this powerful personal record, Larry Chambers recaptures the experience of the war's most brutal on-the-job training, where the slightest noise or smallest error could bring sudden--and certain--death
Keywords: Chambers, Larry, -- 1947-.; United States. -- Army. -- Infantry Regiment, 75th. -- Company L -- History; Vietnam War, 1961-1975 -- Reconnaissance operations, American; Vietnam War, 1961-1975 -- Commando operations -- United States; Vietnam War, 1961-1975 -- Regimental histories -- United States; Vietnam War, 1961-1975 -- Personal narratives, American; A Shau Valley (Vietnam)